Recent Developments in Clinical Applications of Mesenchymal Stem Cells in the Treatment of Rheumatoid Arthritis and Osteoarthritis - Hwang, Joel Jihwan; Rim, Yeri Alice; Nam, Yoojun; Ju, Ji Hyeon (Frontiers in Immunology, 2021)
Mesenchymal stem cell (MSC) therapies have been used as cell-based treatments for decades, owing to their anti-inflammatory, immunomodulatory, and regenerative properties. With high expectations, many ongoing clinical trials are investigating the safety and efficacy of MSC therapies to treat arthritic diseases. Studies on OA have shown positive clinical outcomes, with improved joint function, pain level, and quality of life. The largely positive outcomes in clinical trials without severe side effects demonstrate that MSCs represent promising tools for arthritis treatment. However, further research is required to investigate its applicability in clinical settings. This review discusses the most recent advances in clinical studies on MSC therapies for osteoarthritis (OA) and rheumatoid arthritis (RA).